KAJIAN FILOSOFI HUKUM INTERNASIONAL BERDASARKAN PEMIKIRAN BRIAN Z.TAMANAHA â€œ A REALISTIC OF LAWâ€ - Lona Puspita (Fakultas Hukum Universitas Tamansiswa Padang, 2020)
The statement about whether the law is still being debated, including the existence of international law as law. Therefore, the authors are interested in analyzing the philosophical studies of international law based on Brian Z. Tamanaha's thinking